Preparation and electrochemical properties of urchin-like MgCo2O4 electrode material - NI Hang; LIU Wanneng; KE Zunjie; TIAN Yu; ZHU Xiaolong; ZHENG Guang (Cailiao gongcheng, 2022)
A spinel type of urchin-like MgCo2O4 electrode material was obtained by facile hydrothermal method. The products were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and electrochemical performance of the products was tested by electrochemical workstation measurements. By changing the hydrothermal reaction time, cluster structure, uniform distribution, together with high density of urchin-like MgCo2O4 material can be synthesized. The results show that as the hydrothermal reaction time reaches 6 h, the structure of MgCo2O4 electrode material is relatively perfect, its size is more uniform, and the electrochemical performance is better. Furthermore, at a current density of 1 mA/cm2, area specific capacitance reaches up to 6.75 F/cm2. Additionally, the specific capacitance is maintained at 88.4% after 1000 cycles at the current density of 20 mA/cm2, showing good cycle performance.